Power Of Valerie's Love In Catherine Hardwicke's Red Riding Hood Movie (2011) : A Psychoanalytic Approach - WIDIASTUTI., YULIANA SUCI (2012)
This research is proposed to analyze a power of love in a film with title Red Riding Hood using Psychoanalytic Approach. There are two objectives. The first is to analyze the film in term of structural analysis and the second is to analyze the film based on Psychoanalytic Approach. The research paper belongs to the qualitative research. The object of the study is the personality of Valerie in Red Riding Hood movie. There are two kinds of data sources used in this research, they are primary and secondary. The primary data is the film itself and the secondary data sources are biography of the author, books and internet. The technique of data collection in this research is summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The outcome of the study shows that the film illustrates a power of love of Valerie. Power of love begins when her mother asks her to marry other man. She disagrees with it. Then, she and her boyfriend plan to run away together. It is when her boyfriend becomes a wolf. She can accept whatever happens to him and she always loves him. Based on the analysis, the writer concludes that the problems of major character cause the conflict of her mental condition. It happens when there is contradiction between Id, Ego and Superego that are creating power of love.